(untitled) (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2022)
Background: Patients with type II diabetes mellitus frequently have altered lipid profiles. Detection of serum high sensitivity C-reactive protein is associated with cardiovascular events in type II DM as the presence of subclinical inflammation. The study was undertaken to observe the fasting serum lipid profile level and its association with serum hs-CRP in type II DM. Materials and methods: A hospital-based observational study was carried out in the Outpatient Department of Endocrinology, Chittagong Medical College Hospital and Department of Biochemistry, Chittagong Medical College. By using non-probability consecutive sampling, a total of 176 participants were enrolled, with 126 type II DM and 50 in the control group. Plasma glucose and serum hs-CRP, fasting serum lipid profile was estimated. Results: The mean serum hs-CRP level in patients with type II DM (9.1 ± 0.36 mg/L) was significantly (p 0.0001) elevated as compared to control (4.3 ± 0.09 mg/L). The result showed an increase in serum total cholesterol, serum triglycerides, serum HDLC and serum LDL-C among the diabetic patients when compared with the healthy control group. Serum hs-CRP was significantly associated with serum TG and serum LDL-C in type II diabetics. Moreover, serum hs-CRP was found to have a significant positive correlation with serum LDL-C and serum TG. Only 77.78% of patients had increased LDL-C but altogether 85.71% of patients had increased serum hs-CRP levels. Conclusion: According to the findings of this study,increased serum hs-CRP was well associated and positively correlated with components of the fasting lipid profile, indicating early identification of cardiovascular risk among type II diabetics. Chatt Maa Shi Hosp Med Coll J; Vol.21 (2); July 2022; Page 35-39